Surface Charge of Supramolecular Nanosystems for In Vivo Biodistribution: A MicroSPECT/CT Imaging Study. Issue 37 (14th August 2020) - Ding, Ling; Lyu, Zhenbin; Louis, Beatrice; Tintaru, Aura; Laurini, Erik; Marson, Domenico; Zhang, Mengjie; Shao, Wanxuan; Jiang, Yifan; Bouhlel, Ahlem; Balasse, Laure; Garrigue, Philippe; et al.
Abstract: Bioimaging has revolutionized medicine by providing accurate information for disease diagnosis and treatment. Nanotechnology‐based bioimaging is expected to further improve imaging sensitivity and specificity. In this context, supramolecular nanosystems based on self‐assembly of amphiphilic dendrimers for single photon emission computed tomography (SPECT) bioimaging are developed. These dendrimers bear multiple In 3+ radionuclides at their terminals as SPECT reporters. By replacing the macrocyclic 1, 4, 7, 10‐tetraazacyclododecane‐1, 4, 7, 10‐tetraacetic acid cage with the smaller 1, 4, 7‐triazacyclononane‐1, 4, 7‐triacetic acid scaffold as the In 3+ chelator, the corresponding dendrimer exhibits neutral In 3+ ‐complex terminals in place of negatively charged In 3+ ‐complex terminals. This negative‐to‐neutral surface charge alteration completely reverses the zeta‐potential of the nanosystems from negative to positive. As a consequence, the resulting SPECT nanoprobe generates a highly sought‐after biodistribution profile accompanied by a drastically reduced uptake in liver, leading to significantly improved tumor imaging. This finding contrasts with current literature reporting that positively charged nanoparticles have preferential accumulation in the liver. As such, this study provides new perspectives for improving the biodistribution of positively charged nanosystems for biomedical applications. Abstract : Replacing the DOTA cage with the NOTA scaffold to chelate the radionuclide In 3+, the corresponding dendrimer nanosystem completely reverses the zeta‐potential from negative to positive, generates a highly favorable biodistribution profile with a drastically reduced uptake in liver, and exhibits significantly improved tumor imaging.